2012
DOI: 10.1371/journal.pone.0047255
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Staphylococcus aureus Virulence Gene Expression and Biofilm Formation

Abstract: Staphylococcus aureus is a major human pathogen and one of the more prominent pathogens causing biofilm related infections in clinic. Antibiotic resistance in S. aureus such as methicillin resistance is approaching an epidemic level. Antibiotic resistance is widespread among major human pathogens and poses a serious problem for public health. Conventional antibiotics are either bacteriostatic or bacteriocidal, leading to strong selection for antibiotic resistant pathogens. An alternative approach of inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 75 publications
(91 reference statements)
1
73
0
Order By: Relevance
“…Methods were adapted from literature previously described by Karaolis et al (2005), O'Toole (2011) and Ma et al (2012). S. aureus was adjusted to 10 8 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…Methods were adapted from literature previously described by Karaolis et al (2005), O'Toole (2011) and Ma et al (2012). S. aureus was adjusted to 10 8 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…The initial belief that, almost all microbial biofilms have polysaccharides as the major 'sticking' substance has been altered, with increasing highlights the role proteases as enzymes with potential to disassemble already well established biofilms or prevent initial attachment itself that is essential for biofilm formation [41,42]. This review highlighted the role of self-produced extracellular proteases of S. aureus in biofilm dispersal as well as role of commercially available broad spectrum proteases in biofilm disruption of other Gram positive bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…Another analog, CCG-203592, inhibited SK at a level 35-fold greater than that seen with CCG-2979 (8). Subsequent work led to the observation that this and other analogs are also effective against another Gram-positive pathogen, Staphylococcus aureus.…”
Section: Small Molecules That Affect Host-pathogen Interactionsmentioning
confidence: 99%
“…Furthermore, GAS treated with 5 or 50 M CCG-2979 were more susceptible to phagocytosis by host cells. A series of structural analogs of CCG-2979 was generated, and structure-activity relationship (SAR) studies were performed (8,60). The effect of one chemical analog, CCG-102487, on global gene expression was examined by microarray analysis, which demonstrated that expression of 29% of GAS genes in addition to that of ska was altered, with the vast majority of them being reduced in expression.…”
Section: Small Molecules That Affect Host-pathogen Interactionsmentioning
confidence: 99%
See 1 more Smart Citation